A new method for monitoring coal stress while drilling process: theoretical and experimental study. Issue 2 (1st June 2023) - Zheng, Yahua; Zhao, Zhigang; Zhao, Tongbin; Ma, Chengfu; Zhang, Kai; Qi, Yanshan
ABSTRACT: Real-time acquisition of coal stress is the key to early warning and prevention of rock burst. In the drilling process, drilling parameters will change correspondingly with the change of coal stress. This paper, according to the bit drilling coal link, establishes a theoretical model of drilling in order to verify the reliability of the theoretical model of specific work of drilling crushing, use the self-developed drilling measurement experimental device, and develop the drilling tests on raw coal samples under different lateral stresses. Meanwhile, we study the variation law of drilling parameters with coal stress and reveal the energy conversion mechanism of drilling machine energy to drilling chip surface energy. Through parameter analysis of the theoretical model, it is found that the drilling pressure, torque, and rotation speed increase with increasing coal stress, while the drilling speed decreases with increasing coal stress. The drilling test results show that the particle size of drilling cuttings is approximately normally distributed, the surface energy of drilling cuttings, the mechanical energy of drilling rig, and the amount of drilling cuttings all increase with increasing stress. The mechanical energy of drilling rig is mainly converted into surface energy of drilling cuttings in the process of raw coal drilling. In addition, 8.56–33.12% of the mechanical energy is converted into other energy, with the maximum deviation of 21.50% between the coal stress of the drilling test and the theoretical model of fracture drilling. The research results show that most of the deviation percentages were basically around 10% except for a few deviation percentages, which shows that theoretical model can predict the coal stress through drilling parameters, coal rock properties, and bit parameters. The new method proposed in this paper is of great significance for obtaining the stress distribution state of coal in real time and detecting the stress concentration area of coal.